Career guidance and employment issues for neurodivergent individuals: a scoping review and stakeholder consultation - Bölte, Sven; Carpini, Joseph Alexander; Black, Melissa H.; Toomingas, Allan; Jansson, Frida; Marschik, Peter B.; Girdler, Sonya; Jonsson, Marina (Human resource management, 2025)
Growing recognition of neurodivergence amongst individuals poses challenges for career counselors and human resource practitioners when advising, guiding, and supporting the careers of this diverse group. Despite the potential for neurodivergent individuals to contribute to organizations, career guidance for these individuals is a relatively new area. We conducted a multidisciplinary project comprising a scoping review and stakeholder consultation to generate evidence-based recommendations for identifying and supporting career paths that lead to positive employment outcomes for neurodivergent individuals. The scoping review included 78 articles on career guidance and associated employment issues (e.g., facilitators and barriers to employment) for neurodivergent individuals, while stakeholders, including neurodivergent individuals, counselors, and others, provided insights into their employment experiences. Our scoping review yielded nine themes: career guidance practice, predictors of employment, employment interventions, different forms of employment, work barriers and facilitators, strengths and challenges, person-job fit, occupation and industry fit, and employment outcomes. The stakeholder consultations complemented the scholarly themes. Results were interpreted using the Stone and Colella theoretical model of factors influencing the treatment of people with disabilities. The model was extended across educational and work contexts, and to include the nature of occupations and industries. Building on this project and our overarching theoretical model, we map a future research agenda for the study of careers amongst neurodivergent individuals. Specifically, we highlight persistent methodological limitations of the literature before turning to theoretical implications across career stages. We conclude with practical implications for career counselors and human resource practitioners. Ultimately, our review calls for researchers and practitioners to help promote sustainable, high-quality, and fulfilling careers for neurodivergent individuals.
Online verfügbar: 28 October 2024
Gesehen am 08.07.2025
Keywords: Aufsatz in Zeitschrift